Experimental and Numerical Investigation of Termination Impedance Effects in Wireless Power Transfer via Metamaterial - Giovanni Puccetti; Christopher J. Stevens; Ugo Reggiani; Leonardo Sandrolini (Energies, 2015)
This paper presents an investigation of the transmitted power in a wireless power transfer system that employs a metamaterial. Metamaterials are a good means to transfer power wirelessly, as they are composed of multiple inductively-coupled resonators. The system can be designed and matched simply through magneto-inductive wave theory, particularly when the receiver inductor is located at the end of the metamaterial line. However, the power distribution changes significantly in terms of transmitted power, efficiency and frequency if the receiver inductor slides along the line. In this paper, the power distribution and transfer efficiency are analysed, studying the effects of a termination impedance in the last cell of the metamaterial and improving the system performance for the resonant frequency and for any position of the receiver inductor. Furthermore, a numerical characterisation is presented in order to support experimental tests and to predict the performance of a metamaterial composed of spiral inductor cells with very good accuracy.